2020
DOI: 10.1186/s12879-020-05542-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antibiotic treatment of children in a Shanghai tertiary hospital based on point prevalence surveys

Abstract: Background Misuse and overuse of antibiotics by physicians in the treatment of children is common in China. This study aimed to reveal the overall use of antibiotics to treat children hospitalized in four types of pediatric wards. Methods Seven independent point prevalence surveys (PPSs) were conducted in Shanghai Children’s Hospital of Shanghai Jiao Tong University over the period 2012 to 2018. Pediatric ward types were defined general pediatric medical, pediatric surgical, pediatric intensive care units (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
5
0
4
Order By: Relevance
“…We could only make a preliminary estimate based on experience. The top three antibiotics administered in children patients were cephalosporins (43.8%), penicillins (13.2%), and carbapenems (8.7%) [10], which led to changes of gut microbiota in the study. Detailed pre-admission antibiotic use records are still in progress.…”
Section: Discussionmentioning
confidence: 99%
“…We could only make a preliminary estimate based on experience. The top three antibiotics administered in children patients were cephalosporins (43.8%), penicillins (13.2%), and carbapenems (8.7%) [10], which led to changes of gut microbiota in the study. Detailed pre-admission antibiotic use records are still in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Sebanyak 59,6% pasien menerima antibiotik empiris secara irasional. 9 Di Indonesia sendiri penggunaan antibiotik yang irasional masih banyak terjadi. Sebuah penelitian yang dilakukan di rumah sakit pendidikan di Indonesia, 84% pasien menerima terapi antibiotik dan 60% diantaranya menerima terapi antibiotik yang irasional atau tanpa indikasi yang jelas.…”
Section: Penggunaan Antibiotik Pada Anak Dengan Sakit Kritis DI Picuunclassified
“…(10)(11)(12)(13)(14)(15)(16)(17)(18) These drug resistant strains have become global health crises and an emergency. Factors associated with antibiotic use are both community and hospitals based as studies have reported increased use of antibiotics by parents and caregivers as well as health care providers ( (19)(20)(21)(22)(23)(24)(25). It is therefore imperative to monitor and control antibiotic prescribing to ensure judicious use, prevent resistance and reduce cost of healthcare.…”
Section: Introductionmentioning
confidence: 99%